Der morphogenetische Werdegang der Insel Cypern - Schmidt, Wilhelm F. (ERDKUNDE, 1959)
Geological history and morphogenesis can not be considered separately, both are closely connected. Therefore this publication starts with a survey of the up to date geology of Cyprus. Cyprus is situated within a region of young and strong tectonic movements. The main features of the island, Troodos mountains, Kyrenia Range and coastline are apparently due to tectonical facts. The vertical tectonic together with faulting and displacement were more effective than alpine folding. Cyprus is now a relic of the southernmost Tauric Arc, an isolated uplifted block amidst a region of down broken fields, now being part of the sea bottom. Since the upper Miocene the central Troodos was uplifted at least 2000 m. At the S. W. margin of the Troodos Miocene marine deposits are now at 1140 m above sea level. The northern margin was not yet lifted up to such an extent. Pliocene beds in the foothills area of the Troodos were uplifted by 500 m. Early Pleistocene oyster beds can be observed at 300 m above sea level on table hills south of Nicosia. The uplift of the Kyrenia Range was more than 1500 m. The pre-Miocene geology has only effects on the morphological development by certain resistant rock types, which came into a prominent morphological position by tectonical uplift, e. g. the Hilarion limestones with their alpine styled rock walls and ridges though the altitude of the range does not exceed 1000 meters. Morphological significant are also the magnatic rocks of the Troodos by their massive behaviour (serpentines, gabbros) and their parallel structures (diabases). In the south and east of the Troodos mountains the thick, white chalky beds of the Miocene Pakhna series are responsible for the morphological character. The Koronia reef limestone protected a chain of hills along the northern margin of the Troodos. During the interval between upper Miocene and Pliocene there is a strong tectonic activity again. Regression, up lifting and vertical movement are forming the frame of the future island. The Kyrenia Range is overthrusting its southern foreland. The neighbouring Miocene beds are folded. Simultaneously the intense uplift in the Troodos area effects the sedimentary frame of the mountains. In the Pliocene the recent mountainous areas are already above sea level, e. g. the Troodos Island, the arc of islands along the Kyrenia Range belt, the Phano Island etc. The bottom of the Pliocene sea was in constant movement. Between Pliocene and Pleistocene tectonical activity is once again ruling. In the early Pleistocene Cyprus was for some time connected with the Levantine mainland. The mammals which immigrated from the mainland degenerated after the definite breakdown of the landbridge in sub sequent Pleistocene time. The Pleistocene history of Cyprus is characterized by the known climatical fluctuations marked by pluvials and interpluvials. The vast formation of fanglomerates deposited on the pediment on the northside of the Troodos is regarded as a product of the oldest morphogenetical effective Pluvial. A second pluvial is also represented by gravel terraces, but of minor size and quantity. The younger Pleistocene was a period of erosion, partly caused by further uplift and eustatical low sea level. The recent snowline is estimated at 3100 m, that means much higher than the highest elevation of to-day (Olympus 1953 m). The snowline of the last Pluvial would have been at 2400 m. A Pleistocene glaciation was not possible in Cyprus. Yet there must have been a very strong accumulation of snow during the winters down to 1000 m in the Northern Troodos. Its late and rapid melting supplied the enormous quantities of water necessary for transporting the detritus and gravel masses of the fanglomerates. Some examples of the Quaternary morphogenesis are described in detail. And so are the morphology of the Troodos, of the lava belt and of the coast. Remarkable features of this lava belt are the numerous dykes, following a pattern caused by tectonic movements of the resp. volcanic period. There exist excellent coastal terraces along stretches of the coast. They seem to correspond with the analogue Meditteranean coastal terraces, but their age is not yet proved. Along other parts of the coast the Quaternary levels were destroyed by subsequent vertical tectonic. Certain recent tendencies of the morphogenesis are mentioned, e. g. dunes, erosion gullies, landslips etc.